Incompressible flow turbomachines design, selection, applications, and theory - Round, G. F (George Frederick), 1932-
The primary purpose of this book is to provide an integrated overview of incompressible flow turbomachines and their design, in this case pumps and turbines. Theory and empirical knowledge of turbomachines are brought together in detail to form a framework for a basic understanding of this complex subject. A step-by-step approach is used by means of solved problems at the end of each chapter to accomplish this. Presents a clear overview of incompressible flow turbomachines Treats both types of turbomachines in one text Includes a large number of illustative solved problems.